HUMANITY DEGRADATION IN THE NOVELS WRITTEN BY MINANGKABAU ETHNICS - Yasnur Asri; Zulfadhli Zulfadhli; M. Ismail Nasution (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2016)
PENDEGRADASIAN KEMANUSIAAN DALAM NOVEL-NOVEL PENGARANG ETNIS MINANGKABAUAbstractLiterary works is often used as a social portrait of a society. Novels can be used to view a dynamic cultural or social portrait and the spirit of an age. Novels written by Minangkabau ethnic can be considered as a social representation of the society. This study focused only on socio-cultural portrait, especially the phenomenon of degradation of humanity. It is recognized that the degradation of humanity action is influenced by the culture and norms in the society. This study uses sociological theory of literature to reveal the forms of human degradation. In the sociology of literature, literary works can be seen as a reflection of the various phenomena that occur in the community. Thus, it can be said that the author of the novels of Minangkabau ethnic can be seen as a reflection of Minangkabau social condition. The forms degradatian in humanity in the novels are the interpreted and simultaneously studied the messages conveyed by the authors. Based on the analysis, it was found some forms of degradation of the humanity in the novels written by Minangkabau authors before and after the independent day. The forms of human degradation that are: (1) humanity degradation by social class; (2) humanity degrade through human as material; (3) humanity degradation through violence; (4) humanity degradation community based social function; (5) humanity degradation by power; and (6) humanity degradation by matrilineal culture system.Keyword: degradation, Minangkabau novel, literary sociologyAbstrakKarya sastra sering dijadikan potret sosial suatu masyarakat. Novel dapat digunakan untuk melihat suatu dinamika budaya atau potret sosial dan spirit suatu zaman. Novel-novel pengarang etnis Minangkabau dapat dipertimbangkan sebagai representasi sosial suatu masyarakat. Kajian ini hanya memfokuskan pada potret sosial-budaya, khususnya pada fenomena pendegradasian kemanusian. Disadari bahwa tindakan pendegradasian kemanusiaan dipengaruhi oleh budaya dan norma masyarakat. Teori sosiologi sastra digunakan untuk mengungkap bentuk pendegradasian kemanusiaan. Dalam pandangan sosiologi sastra, karya sastra dapat dipandang sebagai refleksi dari berbagai fenomena yang terjadi di masyarakat. Dengan demikian, dapat dikatakan bahwa novel-novel pengarang etnis Minangkabau dapat dipandang sebagai refleksi sosial masyarakat Minangkabau. Bentuk pendegradasian kemanusiaan yang terdapat di dalam novel diinterpretasikan dan sekaligus memaknai pesan-pesan yang disampaikan pengarang. Berdasarkan analisis yang dilakukan, ditemukan beberapa bentuk pendegradasian kemanusiaaan yang diungkapkan dalam novel-novel pengarang etnis Minangkabau sebelum dan sesudah kemerdekaan. Bentuk-bentuk pendegradasian kemanusiaan itu adalah (1) pendegradasi kemanusiaan berdasarkan  kelas sosial; (2) pendegradasi kemanusiaan melalui pembendaan manusia; (3) pendegradasi kemanusiaan melalui kekerasan; (4) pendegradasi kemanusiaan berdasarkan fungsi sosial masyarakat; (5) pendegradasi kemanusiaan berdasarkan kekuasaan; dan (6) pendegradasi kemanusiaan berdasarkan sistem budaya matrilineal.Keyword: degradasi, novel Minangkabau, sosiologi sastra